(untitled) - Taylor, Peter (Zurich, Switzerland, 2001)
This book describes a methodology to improve the quality of education and training in international co-operation: "Participatory curriculum development" is an emerging approach which builds on the experiences of Helvetas in the Social Forestry Support Programme in Vietnam and other Helvetas supported projects in Sri Lanka, Nepal, Bhutan, Lesotho and Kyrgyzstan.
Keywords: Education